ไพโรไลซิสของชีวมวลโดยใช้ตัวเร่งปฏิกิริยาในฟลูอิไดซ์เบดแบบหมุนเวียน - สินีนาฏ รอดจีน (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
Biomass pyrolysis is a more efficient way of thermal conversing biomass into fuel gas, liquid product and char. In this research, pyrolysis experiments were carried out in a circulating fluidized bed reactor with a riser diameter of 2.5 cm and height 165 cm. The biomass used was corn cob. The experiments were designed using two level factorial designs with temperature ranged of 650-850 degree Celsius, corn cob content of feed from 0 to 100 %, catalyst content of feed from 1 to 5 % and Ni load on catalyst from 5 to 9 %. The results showed that when temperature, corn cob content of feed, catalyst content of feed and Ni load on catalyst increased, the percent of hydrogen and carbon monoxide also increased. Carbon dioxide increased slightly. The percent of methane was considerably decreased. The optimum conditions were 850 degree Celsius, corn cob content of feed 100 %, catalyst content of feed 5 % and Ni load on catalyst 9 %. At this condition percentage of hydrogen and carbon monoxide were 52.0 and 18.0 respectively